WELFARE RACISM the discursive dimension. (ROUTLEDGE, 2026)
Welfare racism is a combination of racial discrimination in the welfare system and racist discourses used in the name of the welfare state. Presenting a global overview of discourses of welfare racism across the world by institutional actors, public figures, political parties, and mass media, this book examines the evolution, character, role, and consequences of racialised welfare discourse towards immigrants, asylum seekers, and BIPOC.This volume explores how racialised welfare discourse fuels and legitimises inequality, as well as its role in public policies concerning social citizenship, and its role as a structural element of migration policies and welfare policies. The chapters focus on a variety of global contexts to analyse how welfare racism is linked to the historical development of the welfare state, the dismantling of social welfare in Western countries, the structures and practices of public administration, the intertwining of welfare racism and welfare classism, political discourses, the media, and the role of far-right parties, academics, and professionals in the spread of racialised welfare discourse.Presenting a novel, in-depth study of the phenomenon from a critical racism perspective, this book expands knowledge on the ideological-discursive dimension of welfare racism. It will appeal to scholars, post-graduate students, and professionals with interests in inequality, migration, public discourse, communication, mass media, social policy, and welfare.
Keywords: Public welfare.; Racism in public welfare.; Social service and race relations.; elektronické knihy; electronic books